Mēdlera teleskopa fotogrāfija tomēr eksistē! - Vilks, Ilgonis (Latvijas Universitātes Muzejs, 2020)
Agrāk domāja, ka Latvijas Universitātes Astronomiskā torņa pirmā teleskopa fotogrāfija nav saglabājusies. Veicot rūpīgus meklējumus Latvijas Universitātes Muzejā, tika atrasta vienīgā teleskopa fotogrāfija. Video paskaidro, kā tā tika atrasta.

Previosusly it was thought that no picture of the first telescope installed at the Astronomical Tower of the University of Latvia was preserved. During thorough search at the Museum of the University of Latvia a single picture of the telescope was found. This video explains how the picture was found.
Keywords: Research Subject Categories::NATURAL SCIENCES; museum; history; astronomy; telescope; Riga Politechnic Institute